PELAKSANAAN SHALAT DHUHA DALAM MENINGKATKAN KECERDASAN SPIRITUAL SISWA KELAS 3 MADRASAH IBTIDAIYAH MA'ARIF NU AJIBARANG WETAN - Wahyu Sabilar Rosyad (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
Spiritual intelligence in the world of education has reached a very influential level, because through education students are guided directly and directed towards the goal of developing spiritual intelligence from school efforts such as teaching and learning, school culture, and through various activities outside of learning. The purpose of this research is to find out how the implementation of Dhuha prayer in improving the spiritual intelligence of students in Madrasah Ibtidaiyah especially in class 3. The study was conducted using a descriptive qualitative approach, the setting of this research is in MI Ma'arif NU Ajibarang Wetan Banyumas district in 2020. The subject of this study is a grade 3 teacher. Research data were obtained through observation, interviews, and documentation. The results of research that researchers have obtained is the implementation of Duha prayer to achieve spiritual intelligence optimally. At MI Ma'arif NU Ajibarang Wetan made efforts from various methods, such as exemplary methods, habituation, advice, motivation and so on. In an effort through the implementation of this Dhuha prayer students have experienced a very good change.